Prophylactic antibiotics after endoscopic sinus surgery for chronic rhinosinusitis: a randomized, double‐blind, placebo‐controlled noninferiority clinical trial. Issue 7 (19th December 2020) - Lehmann, Ashton E.; Raquib, Aaishah R.; Siddiqi, Shan H.; Meier, Josh; Durand, Marlene L.; Gray, Stacey T.; Holbrook, Eric H.
Abstract : Background: Surgeons commonly prescribe prophylactic antibiotics after endoscopic sinus surgery (ESS), yet minimal data exist to support this practice. In this study we aimed to assess the impact of post‐ESS antibiotics on infection, quality of life (QOL), and endoscopic scores. Methods: This was a randomized, double‐blind, placebo‐controlled, noninferiority trial comparing amoxicillin‐clavulanate vs placebo after ESS (NCT01919411, ClinicalTrials.gov). Adults (N = 77) with chronic rhinosinusitis (CRS) refractory to appropriate medical therapy who underwent ESS were randomized to antibiotics (N = 37) or placebo (N = 40) and followed clinically (mean ± standard deviation: 1.3 ± 0.3 and 8.8 ± 3.9 weeks postoperatively). At baseline and follow‐up, QOL was measured with 22‐item Sino‐Nasal Outcome Test questionnaires and Lund‐Kennedy endoscopic scores were evaluated. Outcomes were analyzed with repeated‐measures analysis of variance and analysis of covariance and z tests for proportions. Results: Placebo was noninferior to antibiotic prophylaxis with regard to postoperative SNOT‐22 scores (β = 0.18, 2‐tailed p < 0.05). There were no significant differences between the antibiotic and placebo groups in LK score trajectories over time ( p = 0.63) or in postoperative infection rates (2.6% vs 2.4%, respectively; p = 0.96). The rate of diarrhea was significantly higher in the antibiotic group (24.3% vs 2.5%; relative risk = 10.8; p = 0.02). Conclusion: Although statistically underpowered, the results suggest placebo was noninferior to prophylactic antibiotics after ESS for CRS regarding postoperative sinonasal‐specific QOL. There were no significant differences in postoperative endoscopic scores or rates of infection, but the rate of diarrhea was significantly higher in the antibiotic group. These findings add to the growing evidence that routine use of prophylactic postoperative antibiotics does not improve outcomes post‐ESS and significantly increases the rate of diarrhea.